2021
DOI: 10.1186/s13018-021-02405-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of a simple skin stretching system and negative pressure wound therapy in repair of complex diabetic foot wounds

Abstract: The management of complex diabetic foot wounds with large skin defects poses a challenge for surgeons. We presented a simple skin stretching system and negative pressure wound therapy for the repair of complex diabetic foot wounds to examine the effectiveness and safety.A total of 16 patients with diabetic foot ulcers were retrospectively reviewed between January 2015 and October 2020. All patients underwent the treatment by 3 stages. In stage 2, these difficult-to-close wounds of diabetes foot were residual. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Krticka et al 29 also concluded that VSD combined with a dynamic method could be very effective for fasciotomy wound closure in comparison with traditional techniques. Wu et al 30 and Ji et al 31 shared their successful experience about the application of VSD and skin stretching technique in the treatment of diabetic foot wounds. All of the above reports support our hypothesis that the combination of these 2 techniques is advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Krticka et al 29 also concluded that VSD combined with a dynamic method could be very effective for fasciotomy wound closure in comparison with traditional techniques. Wu et al 30 and Ji et al 31 shared their successful experience about the application of VSD and skin stretching technique in the treatment of diabetic foot wounds. All of the above reports support our hypothesis that the combination of these 2 techniques is advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…11 Intermittent negative pressure has been shown 12 to accelerate the formation of granulation tissue more efficiently than if negative pressure is applied continuously. 13…”
Section: Components Of Negative Pressure Therapymentioning
confidence: 99%